2021
DOI: 10.5194/tc-2020-379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 2020 glacial lake outburst flood at Jinwuco, Tibet: causes, impacts, and implications for hazard and risk assessment

Abstract: Abstract. We analyze and reconstruct a recent Glacial Lake Outburst Flood (GLOF) process chain on 26 June 2020, involving the moraine-dammed proglacial lake Jinwuco (30.356° N, 93.631° E) in eastern Nyainqentanglha, Tibet, China. Satellite images reveal that from 1965 to 2020, the surface area of Jinwuco has expanded by 0.2 km2 (+56 %) to 0.56 km2, and subsequently decreased to 0.26 km2 (‒54 %) after the GLOF. Estimates based on topographic reconstruction and sets of published empirical relationships indicate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 58 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Tens of individual GLOF events have been reported since 2017 in different parts of the world including the Hindu Kush-Karakoram-Himalaya (Byers et al, 2019;Yin et al, 2019;Khan et al, 2021;Maharjan et al, 2021;Muhammad et al, 2021), the Tien Shan (Dayirov and Narama, 2020), the Tibetan Plateau (Zheng et al, 2021b), the Tropical Andes (Vilca et al, 2021;Emmer et al, 2022), the Southern Andes (Anyia et al, 2020;Vandekerkhove et al, 2021), the European Alps (Troilo, 2021;Ogier et al, 2021;Stefaniak et al, 2021), Alaska (Kienholz et al, 2020;Abdel-Fattah et al, 2021), British Columbia (Geertsema et al, 2022), Greenland (Tomczyk et al, 2021) and Scandinavia (Andreassen et al, 2022). Recently, Veh et al (2022) compiled globally by far the most complete GLOF inventory (total of >2800 GLOFs until March 2022; available from http://glofs.geoecology.…”
Section: Geographical Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Tens of individual GLOF events have been reported since 2017 in different parts of the world including the Hindu Kush-Karakoram-Himalaya (Byers et al, 2019;Yin et al, 2019;Khan et al, 2021;Maharjan et al, 2021;Muhammad et al, 2021), the Tien Shan (Dayirov and Narama, 2020), the Tibetan Plateau (Zheng et al, 2021b), the Tropical Andes (Vilca et al, 2021;Emmer et al, 2022), the Southern Andes (Anyia et al, 2020;Vandekerkhove et al, 2021), the European Alps (Troilo, 2021;Ogier et al, 2021;Stefaniak et al, 2021), Alaska (Kienholz et al, 2020;Abdel-Fattah et al, 2021), British Columbia (Geertsema et al, 2022), Greenland (Tomczyk et al, 2021) and Scandinavia (Andreassen et al, 2022). Recently, Veh et al (2022) compiled globally by far the most complete GLOF inventory (total of >2800 GLOFs until March 2022; available from http://glofs.geoecology.…”
Section: Geographical Focusmentioning
confidence: 99%
“…On a local scale, a recent trend goes towards better understanding of controls, preconditions and triggers of individual GLOFs and interactions during them (Carrivick et al, 2017;Blauvelt et al, 2020;Vilca et al, 2021), also considering the role of climate and climate change (Zheng et al, 2021b). Numerous studies not only describe, analyse and model the hydrodynamics and geomorphological imprints of GLOFs (e.g.…”
Section: Glof Triggers and Glof Susceptibility Indicatorsmentioning
confidence: 99%
“…Cryospheric hazards occur frequently in the monsooninfluenced Himalayas, including the southeastern Tibetan Plateau (Kääb et al, 2021;Zheng et al, 2021), a region which hosts temperate glaciers that are typically more sensitive to changes in air temperature than continental glaciers on the Plateau interior (Wang et al, 2019). The region has undergone accelerated mass loss and areal reduction of glacier extent in the past two decades (Bolch et al, 2019), and the rate of regional atmospheric warming is above the global average (Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The region has undergone accelerated mass loss and areal reduction of glacier extent in the past two decades (Bolch et al, 2019), and the rate of regional atmospheric warming is above the global average (Yao et al, 2019). The southeastern Tibetan Plateau contains high topographic relief conducive for the development of hazard cascades, and the region has experienced a series of high-magnitude ice-rock avalanches, glacier detachments, and glacial lake outburst floods in recent decades (Tong et al, 2019;Veh et al, 2020;Kääb et al, 2021;Zheng et al, 2021). Furthermore, the region is the focus of consid-erable investment by the Chinese government, including the construction of the high-speed Sichuan-Tibet railway (anticipated completion 2030) and the development of adjacent areas along this emerging economic corridor, which links the cities of Lhasa and Chengdu (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, all three lakes are susceptible to instantaneous or progressive landslides occurring from the adjacent lateral moraines, most notably for Jialongco where active instabilities are clearly evident. Recent studies have shown that large lateral failures, either instantaneous or progressive, can be sufficient 345 to initiate catastrophic process chains where dam geometries are sufficiently prone to erosion (Klimeš et al, 2016;Zheng et al, 2021b).…”
mentioning
confidence: 99%